2015
DOI: 10.1039/c5cc01854d
|View full text |Cite
|
Sign up to set email alerts
|

X-ray crystallography-promoted drug design of carbonic anhydrase inhibitors

Abstract: 1-N-Alkylated-6-sulfamoyl saccharin derivatives were prepared and assayed as carbonic anhydrase inhibitors (CAIs). During X-ray crystallographic experiments an unexpected hydrolysis of the isothiazole ring was evidenced which allowed us to prepare highly potent enzyme inhibitors with selectivity for some isoforms with medical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Isoform-selective inhibitors. 1-N-Alkylated-6-sulfamoyl saccharin derivative that was unintentionally hydrolyzed during X-ray experiment was further developed into the inhibitor showing selectivity between CA isoforms (Ivanova et al, 2015).…”
Section: Para-meta-benzenesulfonamidesmentioning
confidence: 99%
“…Isoform-selective inhibitors. 1-N-Alkylated-6-sulfamoyl saccharin derivative that was unintentionally hydrolyzed during X-ray experiment was further developed into the inhibitor showing selectivity between CA isoforms (Ivanova et al, 2015).…”
Section: Para-meta-benzenesulfonamidesmentioning
confidence: 99%
“…Common variations include the length of the tail and class or characteristics of the chemical substituents used to derivatize the inhibitor [ 5 , 29 ]. Recently, the success of the tail method to produce isoform specific inhibitors was highlighted by the design of SLC-0111, a CA IX-specific inhibitor currently being tested in clinical trials for the treatment of breast cancer [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, Ivanova et al. reported on the spontaneous ring opening of cyclic tertiary sulfonamides under basic (pH= 9) crystallization conditions 33 . Since hCAs do not possess any peptidase activity, they concluded that the base-catalyzed hydrolysis of the saccharin isothiazolone ring happened before the inhibitor entered the active site, and proved their hypothesis by testing both open and closed analogs against a panel of hCAs (hCA I, hCA II, hCA IX and hCA XII).…”
Section: Introductionmentioning
confidence: 99%